Analisis Manajemen Pengadaan Obat di Unit Instalasi Farmasi RS : Literatur Review - Revina Rahmadani; Elfizon Amir; Yuliana S; Budi Hartono (Jurnal Ventilator, 2025)
Good pharmaceutical procurement management can prevent stock shortages, reduce costs, and improve healthcare service quality. However, issues such as medication shortages, delayed procurement, and discrepancies between demand and supply are still common. This literature review aims to analyze pharmaceutical procurement management in hospital pharmacy units. The literature search yielded 10 relevant articles on pharmaceutical procurement management in hospital pharmacy units. The databases used were Google Scholar, ScienceDirect, and Semantic Scholar. The keywords used were management, pharmaceutical procurement, and hospital. The search results underwent a screening process using the PICO elements and the CRAAP method. The findings indicate that pharmaceutical management in various hospitals has shown progress, but still faces challenges such as inaccurate data collection, delayed drug supply, and storage facilities that do not meet standards. Other obstacles include limited funds, inability to pay on time, and a lack of integrated information systems. However, some aspects are well-managed, such as the use of e-purchasing and proper drug storage categorization.